Q: What is 2 yd and 2 ft x 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

There are 3 ft in a yd ...[(9 x 3 = 27) + 1] - [(4 x 3 = 12) + 2] = (28 - 14) = 14 ft OR 4 yd 2 ft

12 ft * 12 ft = 4 yd * 4 yd = 16 sq yards

24 sq yd 1 yd = 3 ft

1 sq yd = 1 yd * 1 yd = 3 ft * 3 ft = 9 sq ft. 11 ft * 9 ft = 11*9 sq ft = 99 sq ft = 99/9 sq yd = 11 sq yd

(12-ft x 18-ft) = (4-yd x 6-yd) = 24 square yards

Related questions

It's 2 x (9 yd 2 ft) + 2 x (5 yd 2 ft) = 2 x (29 ft) + 2 x (17 ft) = 2 x (46 ft) = 92 ft = 30 yd 2 ft

1 yd = 3 ft → 1 sq yd = 1 yd x 1 yd = 3 ft x 3 ft = 9 ft 1 yd = 36 in → volume = 4800 sq ft x 5 in = 4800 ÷ 9 sq yd x 5 ÷ 36 yd = 74 2/27 cu yd ≈ 74.074 cu yd.

3 ft = 1 yd volume = 12 ft x 12 ft x 2 ft = 12 ÷ 3 yd x 12 ÷ 3 yd x 2 ÷ 3 yd = 10 2/3 cu yd ≈ 10.67 cu yd

64.8 square feet 36 in = 1 yd 1 cu yd = 1 sq yd x 1 yd 1 yd = 3 ft 1 sq yd = 1 yd x 1 yd = 3 ft x 3 ft = 9 sq ft volume = area x thickness ⇒ area = volume ÷ thickness = 1 sq yd x 1 yd ÷ 5 in = 1 sq yd x 1 yd ÷ (5 ÷ 36) yd = 7.2 sq yd = 7.2 x 9 sq ft = 64.8 sq ft

3-ft x 6-ft x 9-ft = 1-yd x 2-yd x 3-yd = 6 yd3

3 yards 1 ft.

Given: 1 yard = 3 feet Squaring both sides of the equation: (1 yd.)2 = (3 ft.)2 1 yd.2 = 9 ft.2 Convert: 60 yd.2 X (32 ft.2/12 yd.2) 60 yd.2 X (9 ft.2/1 yd.2) = 540 ft.2 60 square yards = 540 square feet

1 yd = 3 ft9 yd = (9 x 3) = 27 ft9 yd + 2 ft = 27 ft + 2 ft = 29 ft

3ft = 1 yd 1 ft = 1/3 yd 5/12 ft = 5/12 x 1/3 yd = 5/36 yd.

It is a volume 1 yd x 1 yd x 1 yd or 3 ft x 3 ft x 3 ft.

3 ft = 1 yd 36 in = 1 yd ⇒ 50 ft x 7 ft x 4 in = (50 ÷ 3) yd x (7 ÷ 3) yd x (4 ÷ 36) yd = 350/81 cu yd = 426/81 cu yd ≈ 4.321 cu yd

(25 x 14 ft) / (3 ft/yd) = 116 2/3 yd